DEAFNESS AND VISUALITY IN THE TEACHING OF HISTORY: A CASE STUDY OF ACTION RESEARCH - Vieira, Ana Gabriela da Silva (Cadernos de Educação Tecnologia e Sociedade, 2020)
Teaching in bilingual schools for the deaf, due to the specificities of the students served, whose communication occurs mainly through a sign and visual language, has been using visual resources in the classroom. This article discusses the use of these resources in History classes, based on research carried out in 2017, at a school for the deaf in a city in Rio Grande do Sul. This investigation used action research as a methodology, with the objective of to test methodologies and didactic resources for the teaching of History in deaf students. The use of visual resources for teaching history was explored - images, videos, collages, models, etc. - based on discussions in the area of Deaf Studies that understand visual experience as the basis of deaf culture. As results, it was understood that there are different ways of using visual resources, that images cannot be isolated from the content discussed in the classroom, on the contrary, they need to be contextualized so that deaf students are able to appropriate historical knowledge.